EKSPLORASI BRAND EXTENSION NUTRISARI W’DANK PADA KONSUMEN KECAMATAN TAMPAN - Dinda Gentawicara (Sekolah Tinggi Ilmu Ekonomi Riau, 2026)
Abstract: This study aims to explore the influence of brand extension strategy on brand image and consumer purchase intention for NutriSari W'Dank products in Tampan District, Pekanbaru. NutriSari, initially synonymous with cold fruit drinks, extended its brand into the traditional hot beverage category through the W'Dank variant. This study employs an associative quantitative approach. Data were collected via questionnaires distributed to 100 respondents in Tampan District using a purposive sampling technique. Data analysis was conducted using multiple linear regression analysis SPSS. The results indicate that brand extension has a positive and significant effect on the brand image of NutriSari W'Dank. Furthermore, a positively formed brand image is proven to significantly increase consumer purchase intention. Simultaneously, an appropriate brand extension strategy serves as a primary driver in building trust and stimulating purchasing decisions for this instant traditional beverage product at the local level. The practical implications of this research suggest the importance of maintaining parent brand association alignment when expanding into new product categories. Keywords: Brand Extension, Brand Image, Purchase Intention, NutriSari W’Dank, Tampan District.